Glucosylceramide synthase deficiency in the heart compromises β1-adrenergic receptor trafficking. (23rd June 2021) - Andersson, Linda; Cinato, Mathieu; Mardani, Ismena; Miljanovic, Azra; Arif, Muhammad; Koh, Ara; Lindbom, Malin; Laudette, Marion; Bollano, Entela; Omerovic, Elmir; Klevstig, Martina; Henricsson, Marcus; et al.
Abstract: Aims : Cardiac injury and remodelling are associated with the rearrangement of cardiac lipids. Glycosphingolipids are membrane lipids that are important for cellular structure and function, and cardiac dysfunction is a characteristic of rare monogenic diseases with defects in glycosphingolipid synthesis and turnover. However, it is not known how cardiac glycosphingolipids regulate cellular processes in the heart. The aim of this study is to determine the role of cardiac glycosphingolipids in heart function. Methods and results : Using human myocardial biopsies, we showed that the glycosphingolipids glucosylceramide and lactosylceramide are present at very low levels in non-ischaemic human heart with normal function and are elevated during remodelling. Similar results were observed in mouse models of cardiac remodelling. We also generated mice with cardiomyocyte-specific deficiency in Ugcg, the gene encoding glucosylceramide synthase (h Ugcg –/– mice). In 9- to 10-week-old h Ugcg –/– mice, contractile capacity in response to dobutamine stress was reduced. Older h Ugcg –/– mice developed severe heart failure and left ventricular dilatation even under baseline conditions and died prematurely. Using RNA-seq and cell culture models, we showed defective endolysosomal retrograde trafficking and autophagy in Ugcg -deficient cardiomyocytes. We also showed that responsiveness to β-adrenergic stimulation was reduced in cardiomyocytes from h Ugcg –/– mice and that Ugcg knockdown suppressed the internalization and trafficking of β1-adrenergic receptors. Conclusions : Our findings suggest that cardiac glycosphingolipids are required to maintain β-adrenergic signalling and contractile capacity in cardiomyocytes and to preserve normal heart function. Graphical Abstract: